Transient neurologic symptoms after spinal anesthesia with lidocaine versus other local anesthetics: A systematic review of randomized, controlled trials - Dusanka Zaric (2018)
Lidocaine has been used for spinal anesthesia since 1948, seemingly without causing concern. However, during the last 10 years, a number of reports have appeared implicating lidocaine as a possible cause of neurologic complications after spinal anesthesia. Follow-up of patients who received uncomplicated spinal anesthesia revealed that some of them developed pain in the lower extremities - transient neurologic symptoms (TNS). In this study, we sought to compare the frequency of 1) TNS and 2) neurologic complications after spinal anesthesia with lidocaine with that after other local anesthetics. Published trials were identified by computerized searches of The Cochrane Library, MEDLINE, LILAC, and EMBASE and by checking the reference lists of trials and review articles. The search identified 14 trials reporting 1347 patients, 117 of whom developed TNS. None of these patients showed signs of neurologic complications. The relative risk for developing TNS after spinal anesthesia with lidocaine was higher than with other local anesthetics (bupivacaine, prilocaine, procaine, and mepivacaine), i.e., 4.35 (95% confidence interval, 1.98-9.54). There was no evidence that this painful condition was associated with any neurologic pathology; in all patients, the symptoms disappeared spontaneously by the 10th postoperative day. ©2005 by the International Anesthesia Research Society.